The Effect of Financial Performance on Firm Value with Dividend Policy as a Mediation Variable - Sukma Irdiana; Kusnanto Darmawan; Kurniawan Yunus Ariyono; Mohammad Noor Khairullah (Enrichment : Journal of Management, 2022)
A well-prepared abstract enables the reader to identify the basic content. This study aims to examine the effect of financial performance on firm value through dividend policy. Financial performance uses the current ratio, debt equity ratio and return on assets. While the price to book value, and the dividend payout ratio. This type of research is quantitative research. The data collection technique in this study uses the company's financial reports from the Indonesia Stock Exchange (IDX). The sample in this study was obtained using a purposive sampling method. Based on the purposive sampling method, 90 samples were obtained from corporate objects that fall into the Blue Chips category from 2016-2021. The analytical method uses SPSS version 21. The results show that liquidity and profitability do not have a positive effect on dividend policy. Solvability has a negative effect on dividend policy. For liquidity, solvency, profitability and dividend policy have no positive effect on firm value. Meanwhile, the dividend policy intervening variables cannot mediate liquidity, solvency, and profitability on firm value.